Radiocarbon dating and its applications in Quaternary studies - I. Hajdas (Eiszeitalter und Gegenwart, 2008)
This paper gives an overview of the origin of 14C, the global carbon cycle, anthropogenic impacts on the atmospheric 14C content and the background of the radiocarbon dating method. For radiocarbon dating, important aspects are sample preparation and measurement of the 14C content. Recent advances in sample preparation allow better understanding of long-standing problems (e.g., contamination of bones), which helps to improve chronologies. In this review, various preparation techniques applied to typical sample types are described. Calibration of radiocarbon ages is the final step in establishing chronologies. The present tree ring chronology-based calibration curve is being constantly pushed back in time beyond the Holocene and the Late Glacial. A reliable calibration curve covering the last 50,000-55,000 yr is of great importance for both archaeology as well as geosciences. In recent years, numerous studies have focused on the extension of the radiocarbon calibration curve (INTCAL working group) and on the reconstruction of palaeo-reservoir ages for marine records.